Iodine deficiency and real-life supplementation ineffectiveness in Polish pregnant women and its impact on thyroid metabolism - Filipowicz, Dorota; Szczepanek-Parulska, Ewelina; Mikulska-Sauermann, Aniceta A.; Karaźniewicz-Łada, Marta; Główka, Franciszek K.; Szymanowski, Krzysztof; Ołtarzewski, Mariusz; Schomburg, Lutz; Ruchała, Marek (Frontiers in Endocrinology, 2023)
Introduction. Iodine is a pivotal component of thyroid hormones and its deficiency leads to negative pregnancy outcomes. Therefore, during gestation, additional iodine supplementation is recommended. Objectives. The study updated on iodine status during pregnancy in western Poland, and evaluate iodine supplementation effectiveness in relation to thyroid function of mothers and newborns. Patients and methods. A total of 91 women were recruited before delivery over 2019-2021. The supplements of diet intake was declared during the medical interview. Thyroid parameters (TSH, ft3, ft4, a-TPO, a-Tg) were measured in mothers’ serum and in the cord blood of newborns after birth. Urinary iodine concentration (UIC) and urine/creatinine (UIC/crea) ratio were assessed from single urine samples by validated high-performance liquid chromatography with ultraviolet detection (HPLC-UV). Neonatal screening TSH from dried blood spot was analyzed. Results. Pregnant women had a median (IQR) UIC of 106 (69 - 156) µg/L and UIC/crea ratio of 104 (62 - 221) µg/g, expressing iodine deficiency in 71.5 % according to UIC and 56% considering UIC/crea, whereas up to 18 % had severe iodine deficiency. The iodine supplementation ratio was 68%. The supplemented group had higher maternal ft4 than the non-supplemented group, but no significant difference in UIC was found. Patients with sufficient UIC/crea had the lowest TSH and a-TPO levels. Screening TSH was above 5 mIU/L in 6% of children. Conclusions. Despite national salt iodisation and recommendation to supplement iodine during gestation, the microelement status and real-life intake revealed the ineffectiveness of the current iodine-deficiency prophylaxis model in pregnancy.